A Study on Adsorption Efficiency of Methylene Blue Dye using Adsorbent Material Prepared from Water Hyacinth - Phowan, Naphat (Srinakharinwirot University Engineering Journal, 2020)
An adsorbent for methylene blue dye (MB) adsorption in wastewater was prepared from water hyacinth. The adsorbent is prepared from water hyacinth powder with a particle size smaller than 2 mm, water hyacinth pretreated with sodium hydroxide (NaOH) and water hyacinth modified to biochar. Highest Iodine Number (I.N.) is 636.30±4.16 mg g-1 was obtained when water hyacinth was modified to biochar. The chemical structure of the three adsorbents was characterized by the Fourier Transform Infrared Spectroscopy (FT – IR) also found similar spectra of the adsorbents that showed important functional groups in cellulose. Moreover, the effects of contact time, adsorbents dose on the adsorption capacity, and adsorption isotherm were studied. The results indicated that the optimum conditions were the contact time of eight hours and the adsorbents dose of 20 g L-1. The adsorption isotherm of MB by the adsorbents was best described by the Langmuir isotherm which indicated the monolayer. The adsorption capacity of MB by biochar was the best efficiency, with an adsorption capacity of 21.88 mg g-1.